Optimizing Fifth-Grade Students’ Mathematics Learning Outcomes Through the Teaching at the Right Level (TARL) Approach - Irna Helvianti Helvianti; Sati; Abdul Karim (Elementary Teacher Education Program, Majalengka University, 2026)
This study was conducted based on classroom observations and interviews with the fifth-grade teacher at SD Negeri 3 Sedong Lor, Cirebon Regency. The findings indicated that students’ mathematics learning outcomes were still unsatisfactory, particularly in addition operations involving whole numbers. One of the contributing factors was the implementation of uniform instruction that did not adequately accommodate differences in students’ learning readiness and abilities. As a result, many students experienced difficulties in understanding concepts, analyzing problems, and drawing conclusions during learning activities. Therefore, this study aimed to examine the effectiveness of the Teaching at the Right Level (TaRL) approach in improving students’ mathematics learning outcomes. The study employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The participants consisted of 23 fifth-grade students selected through total sampling. Data were collected using observation sheets and learning achievement tests. The results revealed improvements in several aspects of the learning process, including the quality of teaching modules, teacher performance, student learning activities, and cognitive achievement. Statistical analysis showed a significant difference between students’ scores before and after the implementation of TaRL (t = 107.861; p < 0.000). These findings indicate that the TaRL approach effectively supports mathematics learning by aligning instruction with students’ actual learning needs and levels of understanding